The Primary Sources of Entrepreneurial Passion Beyond Traditional Typologies - Özgen, Özge; Hızarcı, Ayça; Demirel, Banu (International Journal of Contemporary Economics and Administrative Sciences, 2024)
The objective of this study is to explore how entrepreneurs personally experience and interpret their passion throughout their entrepreneurial journey, identify the primary sources of entrepreneurial passion, uncover additional domains of entrepreneurial passion beyond traditional typologies, and examine the influence of culture on entrepreneurial passion. This qualitative study of 23 entrepreneurs and content analysis of the interviews indicate that entrepreneurial passion is multi-faceted, with autonomy, innovation, and relationship with stakeholders emerging as key sources of entrepreneurial passion. Passion for autonomy and self-development are also unexplored concepts in entrepreneurial passion literature by extending the traditional typologies. Finally, this study associated the dimensions of culture with sources of entrepreneurial passion.